2019
DOI: 10.1002/aur.2073
|View full text |Cite
|
Sign up to set email alerts
|

Tactile hypersensitivity and GABA concentration in the sensorimotor cortex of adults with autism

Abstract: Sensory hypersensitivity is frequently encountered in autism spectrum disorder (ASD). Gamma‐aminobutyric acid (GABA) has been hypothesized to play a role in tactile hypersensitivity. The aim of the present study was twofold. First, as a study showed that children with ASD have decreased GABA concentrations in the sensorimotor cortex, we aimed at determining whether the GABA reduction remained in adults with ASD. For this purpose, we used magnetic resonance spectroscopy to measure GABA concentration in the sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
69
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 82 publications
13
69
2
Order By: Relevance
“…Consistent with recent pharmacological work in nonhuman primates 22 , our recent study using lorazepam (a GABAA receptor modulator) in NT humans 1 showed that strengthening inhibition yields weaker, rather than stronger spatial suppression during motion discrimination. Our current MRS results are in line with previous observations of normal GABA+ levels within visual cortex in people with autism 13,15,17 (but see 14 for a more nuanced report). Thus, although there is evidence for weaker inhibition in mouse models of ASD 7,[9][10][11] , our results do not support the notion that weaker inhibition drives weaker neural suppression in humans with ASD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with recent pharmacological work in nonhuman primates 22 , our recent study using lorazepam (a GABAA receptor modulator) in NT humans 1 showed that strengthening inhibition yields weaker, rather than stronger spatial suppression during motion discrimination. Our current MRS results are in line with previous observations of normal GABA+ levels within visual cortex in people with autism 13,15,17 (but see 14 for a more nuanced report). Thus, although there is evidence for weaker inhibition in mouse models of ASD 7,[9][10][11] , our results do not support the notion that weaker inhibition drives weaker neural suppression in humans with ASD.…”
Section: Discussionsupporting
confidence: 92%
“…However, evidence for a widespread reduction in inhibition is either indirect or inconclusive. For example, there is evidence for decreased inhibition from genetic models of ASD in mice 7,[9][10][11] , but results in humans remain equivocal 8,[12][13][14][15][16][17] . An alternative is that modulatory processes that suppress neural responses, but do not rely directly on neural inhibition, are either disrupted or differentially engaged in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have investigated differences in GABA and showed no differences in the VIS [Gaetz et al, ; Robertson et al, ], striatum [Harada et al, ; Horder et al, ], and medial prefrontal cortex [Horder et al, ]. However, other studies have reported lower GABA levels in other areas, such as the sensorimotor cortex [Puts et al, ; Sapey‐Triomphe et al, ], frontal lobe [Harada et al, ; Kubas et al, ], and auditory cortex [Gaetz et al, ; Port et al, ; Rojas et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have investigated differences in GABA and showed no differences in the VIS [Gaetz et al, 2014;Robertson et al, 2016], striatum [Harada et al, 2011;Horder et al, 2018], and medial prefrontal cortex [Horder et al, 2018]. However, other studies have reported lower GABA levels in other areas, such as the sensorimotor cortex [Puts et al, 2017;Sapey-Triomphe et al, 2019], frontal lobe [Harada et al, 2011;Kubas et al, 2012], and auditory cortex [Gaetz et al, 2014;Port et al, 2017;Rojas et al, 2014]. Although these mixed results may result from regionspecific group differences, methodological variability across studies may also contribute to these inconsistent findings.…”
Section: No Evidence Of Reduced Gaba Concentrationsmentioning
confidence: 97%
See 1 more Smart Citation